(untitled) (Iranian Journal of Kidney Diseases, 2009)
Introduction. The latent nature of chronic kidney disease (CKD) in primary stages precludes early diagnosis. This necessitates plans such as screening, but we should first introduce CKD as a public health problem. This study was designed to define the burden of CKD in Iran. Materials and Methods. We calculated disability-adjusted life years (DALYs) according to the World Health Organization’s practical guidelines for national burden of disease studies. The sum of years of life lost and years lived with disability were estimated for CKD stages 1 to 4 and end-stage renal disease (ESRD) based on the national registry data and the published reports about CKD in Iran in 2004. Results. Over 700 000 people were estimated to have CKD in Iran in 2004 and 61 000 new cases of CKD were anticipated. The prevalence rate of CKD was estimated to be 1083 and its incidence rate was 173.5 per 100 000 population. Chronic kidney disease was responsible for 1 145 654 DALYs. The highest DALYs for stages 1 to 4 of CKD were due to unknown etiology, diabetes mellitus, and hypertension (382 000 years, 347 400 years, and 311 800 years, respectively). The DALY for ESRD and CKD stages 1 to 4 were 21 490 years and 1 124 164 years, respectively. Conclusions. The present study provides an estimate of the burden of CKD in Iran. As CKD can be controlled by practical cost-effective plans, we strongly recommend the information given by this study be considered for future action plans.